“Making Peace with Our Bodies”: A Qualitative Analysis of Breast Cancer Survivors' Experiences with Qigong Mind–Body Exercise - Osypiuk, Kamila (J Altern Complement Med, 2020)
Objectives: Breast cancer treatment leaves breast cancer survivors (BCS) with an array of lasting side effects, including persistent postsurgical pain (PPSP). In this study, we explored the perceptions of BCS with PPSP as they learned Qigong mind-body exercise (QMBE), a multimodal practice rooted in Traditional Chinese Medicine. Methods: Participants included 18 female BCS treated for stage 0–III breast cancer and experiencing PPSP. Participants were taught QMBE over 12 weeks. Semi-structured interviews were conducted before and after the intervention. Results: BCS disclosed a disconnect between mind and body that emerged during treatment. They perceived QMBE as moving meditation, which enabled them to reconnect mind and body, lessen their pain, and make peace with their bodies. Conclusion: These women's experiences both inform the promise of integrating QMBE and related mind-body exercise into PPSP clinical practice guidelines and suggest new areas of research regarding the role of multimodal interventions for holistic healing in BCS.